Pengaruh latihan wall body reaction terhadap latihan reaksi di cabang olahraga anggar - Ismalasari, Rini; Primanata, Dani; Bulqini, Arif; Rusdiawan, Afif; Lestari, Bhekti (Universitas Hamzanwadi, 2024)
The purpose of this study was to determine the relationship of whole-body reaction training to reaction training, In fencing training, speed and accuracy are key factors to achieve victory in matches. Therefore, wall body reaction tools have been developed to help fencers improve their reaction ability. This research is correlational research, the method used is a survey with data collection techniques using tests and measurements. The sample of this study was Surabaya and Sidoarjo fencers, totaling 13 athletes. data analysis using the help of SPSS application Version 26.00. The results of this study showed that there was a relationship between visual Whole Body Reactions exercise with Reactive Exercise of 0.373 with a value of rx1.y = 0.373 > r (0.05) (13) = 0.553. There is a relationship between visual Whole-Body Reactions and Reaction Exercise of 0.373 with values of rx1.y = 0.373 > r (0.05) (13) = 0.553. and There is a relationship between audio and visual Whole-Body Reactions with Reaction Exercises of 0.453, with values rx3.y = 0.453 > r (0.05) (13) = 0.553. The conclusion of this study is that there is a relationship between whole body reaction exercise and reaction training.